2022
DOI: 10.5194/acp-22-8659-2022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dust on rainfall over the Red Sea coast based on WRF-Chem model simulations

Abstract: Abstract. Water is the single most important element of life. Rainfall plays an important role in the spatial and temporal distribution of this precious natural resource, and it has a direct impact on agricultural production, daily life activities, and human health. One of the important elements that govern rainfall formation and distribution is atmospheric aerosol, which also affects the Earth's radiation balance and climate. Therefore, understanding how dust compositions and distributions affect the regional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 116 publications
0
29
0
Order By: Relevance
“…We also run simulations with and without dust to understand the effect of dust on rainfall during the case study. We conduct an additional set of simulations without aerosol-radiation interaction in order to calculate the direct and indirect effects of dust on rainfall as in Parajuli et al (2022b). The dust effects were calculated from the above two sets of simulations, the first being with and without dust simulations (F1 and F2) that included both direct and indirect effects and the second set being with and without dust (F3 and F4) simulations with restricted aerosol-radiation interactions (aer_ra_feedback = 0).…”
Section: Methodsmentioning
confidence: 99%
“…We also run simulations with and without dust to understand the effect of dust on rainfall during the case study. We conduct an additional set of simulations without aerosol-radiation interaction in order to calculate the direct and indirect effects of dust on rainfall as in Parajuli et al (2022b). The dust effects were calculated from the above two sets of simulations, the first being with and without dust simulations (F1 and F2) that included both direct and indirect effects and the second set being with and without dust (F3 and F4) simulations with restricted aerosol-radiation interactions (aer_ra_feedback = 0).…”
Section: Methodsmentioning
confidence: 99%
“…Dust particles can further affect the rainfall patterns through various direct and indirect pathways (Koren et al, 2005;Jin et al, 2015;Parajuli et al, 2022). Changes in rainfall patterns can have broader and long-term consequences because the entire biosphere directly depends upon rainfall for its survival.…”
Section: Dust Direct Semi-direct and Indirect Effectsmentioning
confidence: 99%
“…The direct and indirect effects of dust on rainfall was quantified recently by Parajuli et al (2022). The study which used WRF-Chem simulations over the Red Sea coastal region showed different responses of dust on rainfall for extreme and normal rain events.…”
Section: Dust Direct Semi-direct and Indirect Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hui et al, 2008) and through a modulation of synoptic-scale and mesoscale atmospheric circulations (e.g. Jin et al, 2021;Parajuli et al, 2022). Not being able to predict dust-induced cirrus formation can lead to large forecast errors for the solar irradiance at the surface, even in day-ahead forecasts.…”
Section: Introductionmentioning
confidence: 99%